Pengaturan Sistem Manajemen Anti Penyuapan (SMAP) Dalam Pengadilan Tata Usaha Negara - Damayanti, Ita; Romdanah, Siti; Rahayu, Nonik; N, Nabilah; Al Hadad, Muhammad; Salam, Nino Alfitra (Media Hukum Indonesia (MHI), 2025)
The implementation of the Anti-Bribery Management System (SMAP) based on ISO 37001:2016 in the State Administrative Court (PTUN) is a strategic step by the Supreme Court of the Republic of Indonesia in building a clean, transparent, and integrity-based justice system. The implementation of SMAP has been carried out in a number of PTUNs, such as the Jakarta, Serang, and Manado PTUNs, through the establishment of the Anti-Bribery Compliance Unit (UKAP), the preparation of risk registers, internal training, and the provision of reporting mechanisms such as the Whistleblowing System (WBS) and the SIWAS application. Structural evaluations show compliance with ISO standards, but its substantive effectiveness still faces obstacles, including low reporting of violations, lack of employee understanding, and the lack of internalization of an anti-corruption culture as a whole. This study aims to analyze the regulation of SMAP in PTUN and evaluate its effectiveness as an instrument for preventing corruption in the administrative justice system. The research method used is normative juridical with a statute approach and conceptual approach, supported by literature studies. The results of the study show that the success of SMAP implementation is not only determined by administrative compliance, but also by the internalization of integrity values, the involvement of external audits, and strong leadership support. Therefore, strengthening an anti-bribery culture on an ongoing basis is a prerequisite for building an accountable and publicly trusted judiciary.